Fire resistance of tree species in Bukit Soeharto Education Forest, East kalimantan, Indonesia - Delmy, A. (Center for International Forestry Research, 2001)
The effects of the forest fire on anatomical and ecophysiological resistance of tree species was investigated in Bukit Soeharto Education Forest, an area about 5000 ha, in East Kalimantan, Indonesia. The forest was impacted seriously by forest fire in 1998. This forest land is dominated by Dipterocarpaceae species, especially Shorea spp., with some Dryobalanops, Cotylelobium and Anisoptera species. The investigation was conducted in a single plot of burned primary forest with scattered gaps. The gaps had mixed pioneer and non-pioneer species, such as Eusideroxylon zwageri, Macaranga hypoleuca, Shorea laevis, Macaranga gigantea, Palaquium rostratum and Polyalthia sumatrana. Tree density (>10 cm diameter) was 337 ha-1. After the forest fire there were 147 dead trees ha-1 mainly Macaranga hypoleuca, Macaranga gigantea, Shorea laevis, Palaquium rostatum, Polyalthis sumatrana and Hydnocarpus polypetala. There were 41 sprouted tree species ha-1, mainly Eusideroxylon zwageri, Litsea sp., Durio carinatus, Gironniera nervosa and Diospyros curaniopsis. There were 151 living, but unsprouted, trees ha-1 dominated by Eusideroxylon zwageri, Shorea laevis, Shorea palembanica, Palaquium macrophyllum and Shorea smithiana. The numbers of dead and sprouting trees were related to the fire conditions and only some tree species had sprouts. Bark thickness was positively correlated with fire resistance and the healthiness of the trees in the canopy.